Efecto de la edad de la vareta en el prendimiento de cacao CC-51 etapa de vivero en el cantón Quinsaloma - Holguín Valencia, Marcelo Lorenzo (2012)
This research was conducted in the Campus Balsería on the farm owned by Mr. Marcelo Holguin Valencia, located at Km 14 of the track The Ercilia Quinsaloma, Canton Quinsaloma, Province of Los Rios. The geographic location of the house is 1 ° 3 '18'' south latitude and 79 ° 25' 24'' west longitude at a height of 73 meters. They pose the following general objective assess the effect of the age of the scion in the grafting of cacao by grafting CCN 51 pick in the canton side Quinsaloma and specific. Determine the agronomic performance of the graft side barbed CCN-51 cocoa with different ages of crochet and see to what extent the age of the scion influence the arrest of lateral spike grafts CCN-51 cocoa also determine the relationship benefit / cost of the treatments under study. Subject to the following hypothesis: When using braces grafts CCN-51 cocoa two months you get a high engraftment and buds will have greater force. By grafting with scions of cocoa CCN 51 two months we represent better value for money. Raised the following treatments: T.1 at 90 days age of 80 days T.2 crochet age of 70 days old crochet T.3 of crochet T. April 60 d age of crochet. Treatments were arranged in a Random block design (CRD) with four treatments and four replicates to determine differences among treatment means were used Tukey's multiple test at 0.05% chance. The experimental unit. They employ a total of 480 plants (patterns) of CCN-51 cocoa aged months each experiment will consist of 30 floors each treatment with four replications with a total of 120 plants per treatment: At 30, 45, 60 periods in days, percentages of surviving the shoot height (cm), leaf number (No.), leaf length (cm) Thickness of shoots (mm). The results show the age of the scion in the grafting of cacao CCN-51, T.4 60 days was the best result was obtained on all variables compared to other treatments T.1 at 90 days, T .2 of 80 days and 70 days T.3 age of crochet, we obtained the arrest of the age of 60 days crochet was reported that the yield performance presented the 99.00 and 98% of seizure, in the Height 15.73 cm buds, leaf length 27.68 cm, 10.75 cm sheet number. 5.23 mm thickness of the outbreak. The best value and benefit / cost ratio belonged to T. 4 (0.33 USD) gave the best economic result in the effect of age on engraftment crochet CCN-51 cocoa. According to the results obtained are accepted hypotheses that indicate: that the use of braces grafts CCN-51 cocoa two months of age showed a high engraftment. By grafting with scions of cocoa CCN - 51 in two months we represent better value for money.